2013
DOI: 10.1007/s12178-013-9184-9
|View full text |Cite
|
Sign up to set email alerts
|

Syndesmosis injuries

Abstract: Traumatic injuries to the distal tibiofibular syndesmosis commonly result from high-energy ankle injuries. They can occur as isolated ligamentous injuries and can be associated with ankle fractures. Syndesmotic injuries can create a diagnostic and therapeutic challenge for musculoskeletal physicians. Recent literature has added considerably to the body of knowledge pertaining to injury mechanics and treatment outcomes, but there remain a number of controversies regarding diagnostic tests, implants, techniques,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 65 publications
(63 reference statements)
0
42
0
1
Order By: Relevance
“…Anatomic reconstruction and operative fixation of the distal tibiofibular syndesmosis is critical to achieving an optimal outcome, and misdiagnosis or inadequate management of the syndesmosis injury can lead to chronic ankle instability, with persistent ankle pain, early post-traumatic arthritis and, eventually, arthritic changes in the ankle joint [5][6][7]. An ideal implant to stabilize the tibiofibular syndesmosis should allow early mobilization for weightbearing and be strong enough to maintain reduction in the syndesmosis [8], in clinical practice, various different strategies have been used throughout the years, however, there is still no consensus about the optimal method of treatment [9]. The screw fixation is a simple method and provides rigidity of the distal tibiofibular syndesmosis, and it has been considered the standard management [10]; however, this rigid fixation method may be problematic in allowing physiologic motion of the syndesmosis and sometimes screw breakage may occur [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Anatomic reconstruction and operative fixation of the distal tibiofibular syndesmosis is critical to achieving an optimal outcome, and misdiagnosis or inadequate management of the syndesmosis injury can lead to chronic ankle instability, with persistent ankle pain, early post-traumatic arthritis and, eventually, arthritic changes in the ankle joint [5][6][7]. An ideal implant to stabilize the tibiofibular syndesmosis should allow early mobilization for weightbearing and be strong enough to maintain reduction in the syndesmosis [8], in clinical practice, various different strategies have been used throughout the years, however, there is still no consensus about the optimal method of treatment [9]. The screw fixation is a simple method and provides rigidity of the distal tibiofibular syndesmosis, and it has been considered the standard management [10]; however, this rigid fixation method may be problematic in allowing physiologic motion of the syndesmosis and sometimes screw breakage may occur [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…One potential mode of fixation for this pathologic entity is the suture button technique. Proponents of this method have described equivocal outcomes with a decreased risk of hardware failure compared with screw fixation, a reduced rate of required secondary surgery for hardware removal, and the allowance of some anatomic motion about the syndesmotic complex after insertion (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%
“…However, suture-anchor fixation is cost-effective and leads to fewer surgical risks during subsequent surgery to remove internal fixation implants. Hunt performed a 12-month follow-up study in 347 patients between 2000 and 2006 and found that postoperative ankle function was poorer in patients with screw fixation of the distal tibiofibular syndesmosis than in patients without fixation 23 . In addition, Miller et al showed that postoperative ankle function improved slightly after the removal of screws for fixation of a distal tibiofibular syndesmosis 24 .…”
Section: Management Of the Distal Tibiofibular Syndesmosismentioning
confidence: 99%